2015
DOI: 10.1680/adcr.13.00092
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behaviour of sulfate in early cement hydration

Abstract: This paper investigates the adsorption behaviour of sulfate on calcium-silicate-hydrate (C-S-H) gel, which is significantly related to cement hydration and delayed ettringite formation. Aqueous sulfate solution from cement paste and prepared calcium-silicate-hydrate samples are used to take other ions and cement hydration into account.The effects of gypsum content, temperature and alkalinity on dissolution and adsorption behaviours of sulfate in cement paste are studied. The results show that higher gypsum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, some studies [16,52] showed that the shrinkage properties of cement-based materials had little difference when the single potassium mirabilite (K 2 SO 4 ) and anhydrous mirabilite (Na 2 SO 4 ) prepared by high-temperature calcination were incorporated. It can be confirmed that the effect of soluble alkali sulfates obtained on the shrinkage property of cement-based materials is more profound than that of the original alkali sulfates in cement particles, which may be attributed to the different crystal types of alkali sulfates [16,52]. Furthermore, the effect of different types of alkali sulfates on the autogenous shrinkage of cement-based materials is more profound than that on drying shrinkage.…”
Section: The Shrinkage Properties Of Cement-based Materials With Different Types Of Alkali Sulfatesmentioning
confidence: 99%
“…However, some studies [16,52] showed that the shrinkage properties of cement-based materials had little difference when the single potassium mirabilite (K 2 SO 4 ) and anhydrous mirabilite (Na 2 SO 4 ) prepared by high-temperature calcination were incorporated. It can be confirmed that the effect of soluble alkali sulfates obtained on the shrinkage property of cement-based materials is more profound than that of the original alkali sulfates in cement particles, which may be attributed to the different crystal types of alkali sulfates [16,52]. Furthermore, the effect of different types of alkali sulfates on the autogenous shrinkage of cement-based materials is more profound than that on drying shrinkage.…”
Section: The Shrinkage Properties Of Cement-based Materials With Different Types Of Alkali Sulfatesmentioning
confidence: 99%
“…The sulfate ions adsorption onto CSH products is regarded as one key factor for the possible delayed ettringite formation (DEF) in cement-based materials. Ma et al (2015) studied the adsorption behaviours of CSH through synthesised CSH gels in their contribution. The basic observations were that the adsorption of sulfate ions was favoured by higher sulfate ion concentration in aqueous phases as well as the temperature rise, and the high alkalinity of aqueous hindered the sulfate sorptivity of CSH by electrostatic interactions.…”
mentioning
confidence: 99%